Pemberdayaan Masyarakat di Wisata Edukasi Imah Noong Kampung Areng Kecamatan Lembang Kabupaten Bandung Barat - Hardianto, Seno; Kartika, Titing; Karini, Rieke Sri Rizki Asti (THE Journal : Tourism and Hospitality Essentials Journal, 2018)
Community empowerment is the effort to create and improve the capacity of the community both individually and groups in solving various problems related to efforts for improve the quality of life, independence and prosperity. Community empowerment can be done through the various ways and one of them through the growth and development. This research was conducted in Wisata Edukasi Imah Noong, Kampung Areng Desa Wangunsari Kecamatan Lembang Kabupaten Bandung Barat. The method of this research is descriptive research method with qualitative approach. Data collection method used is field observation, interview and documentation. Primary data source obtained from purposive sampling. Then from the results of this research be obtained a conclusion of action or activities of the community in the implementation of the concept of community empowerment approach through development of tourism, namely strengthening the capacity and role of society, strengthening access and business opportunities, and strengthening of tourism awareness.